The commons in transition - Thomas Sikor (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2002)
The paper analyses the institutional dynamics surrounding common-pool resources in postsocialist Central and Eastern Europe. It is conceived in close conjunction with the case studies reported in the four preceding papers in this series. The purpose of this paper is to frame the individual case inquiries, compare the findings from the four plus two additional case studies, and relate those to broader agrarian and environmental changes in Central and Eastern Europe. The comparative assessment suggests that resource governance has shifted from the previously dominant legal and administrative state hierarchies towards markets. In addition, state power has moved from central governments towards local authorities. The waning and decentralisation of state power has caused the emergence of significant gaps between property legislation and rights-in-practice, which have been particularly stark in weak states. The discrepancy between legal texts and rights-in-practice leads to the exclusion of public and collective interests in favour of private interests in CPR management. It finds its environmental expression in the declining use of water control systems, widespread destruction of water infrastructure, and unfettered conversion of agricultural land for urban sprawl. Thus, the findings attest to the central role of distributive issues in postsocialist privatisation and suggest an additional dimension of distributive conflict: different rights and obligations associated with resources. They also suggest the need for postsocialist governments to be actively involved in the management of common-pool resources for the protection of public and collective interests.
Keywords: 330; Allmenderessource; Institutioneller Wandel; Landwirtschaft; Umweltbewußtsein; Osteuropa